GENDERED SPACE IN THE JAVANESE NOBLE HOUSE OF PANGERAN MERTADIREJA III - Amalia, Yesi Syafira; Marwoto, Irmawati (UI Scholars Hub, 2021)
Javanese traditional house are built to reflect the microcosm and microcosm of the Javanese philosophy of living. For the Javanese, duality and balance are two important concepts, which is reflected spatially through the how their houses are organized: inside and outside, left and right, rest area and activity area, as well as masculine and feminine spaces. This research discusses the meaning of gendered space in the house nDalem Pangeranam Mertadireja III. Gendered space is the main focus of discussion because gendered activities both shape and are shaped by gendered spaces. Ndalem Pangeranan Mertadireja III is a traditional Javanese house built in 1901 by the 17th Banyumas Regent, Pangeran Adipati Aria Mertadireja III. The house is located in Banyumas, Central Java. The purpose of this study is to analyze how gender is reflected in space, and how gendered resistance can then be observed spatially. This research concludes that within the Mertadireja house, masculine spaces are open, clean, and located in the front and right side of the house. In contrary, feminine spaces are closed, dirty, and located in the back and left side of the house. However, resistance is reflected spatially when women make use of masculine spaces.